2019
DOI: 10.24200/jonus.vol4iss2pp1-28
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-Efficacy, Motivation, and Independence on Students’ Entrepreneurial Intentions

Abstract: Entrepreneurship education has been implemented in higher institutions in order to give exposure and develop students’ skills and interest in business. Although entrepreneurship course is taught in many universities, researchers are still arguing whether entrepreneurship education is related to the intention to start a business. This study investigated the impact of self-efficacy, independence, and motivation on entrepreneurial intentions among university students. A total of 496 questionnaires were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 75 publications
1
9
0
3
Order By: Relevance
“…Further, it was found that the need for independence affects EI. This result is consistent with the findings of Omar et al (2019), and Barba-Sánchez and Atienza-Sahuquillo (2018) that found that the need for independence affects EI. Also, this result supports Hessels, Rietveld, and van der Zwan (2017) position that the tendency to be an entrepreneur is greater owing to the need for independence and job control.…”
Section: Structural Modelsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, it was found that the need for independence affects EI. This result is consistent with the findings of Omar et al (2019), and Barba-Sánchez and Atienza-Sahuquillo (2018) that found that the need for independence affects EI. Also, this result supports Hessels, Rietveld, and van der Zwan (2017) position that the tendency to be an entrepreneur is greater owing to the need for independence and job control.…”
Section: Structural Modelsupporting
confidence: 93%
“…Tyszka, Cieślik, Domurat, and Macko (2011) reiterated that entrepreneurs are probably more driven by the need to be independent than any other motivation, which also helps in shaping their intention and actions to start a business of their own. The study by Omar et al (2019) found that the need for independence affects students' intention to start a venture. Barba-Sánchez and Atienza-Sahuquillo's ( 2018) study confirms that the need for independence accounts for the intent to start a new venture.…”
Section: Mediating Role Of the Need For Independence On Entrepreneurial Selfefficacy And Eimentioning
confidence: 99%
“…It is a personality characteristic that motivates someone to face challenges and encourages them to never quit, even in difficult situations. It is an internal driving force that keeps individuals focused on set targets, and so is considered to be essential in developing career choices [35]. It is an exceptional characteristic that distinguishes a person from others, and is based on three dimensions: magnitude, strength, and generality [3].…”
Section: Antecedents Of Entrepreneurial Intentionmentioning
confidence: 99%
“…Karen Esther Tan, Sylvia @ Nabila Azwa Ambad, Sakka Nordin, Jasmine Vivienne Andrew, Nur Syahidah Wong Abdullah Jurnal Intelek Vol. 16, Issue 1 (Feb) 2021 While a study by Omar et al, (2019) on 496 undergraduate students of Universiti Kebangsaan Malaysia (UKM) suggests that entrepreneurial education may be useful in producing high entrepreneurial intentions among students enrolled in higher institutions of education in Malaysia, thus, it can be concluded from the findings that three critical drivers, self-efficacy, the need for independence, and motivation, are significant and are positively associated with entrepreneurial intention, particularly among students at higher institutions of learning. Ekpi and Razak (2015) suggested that skill acquisition, self-motivation, and social influence are other factors that need to be emphasised on top of education support.…”
Section: The Impact Of Education Support and Entrepreneurial Intentionmentioning
confidence: 99%